Energy, exergy, and exergoeconomic evaluation of a novel CCP system based on a solid oxide fuel cell integrated with absorption and ejector refrigeration cycles. (1st March 2021) - Dhahad, Hayder A.; Ahmadi, Samareh; Dahari, Mahidzal; Ghaebi, Hadi; Parikhani, Towhid
Highlights: An innovative energy conversion system operated by SOFC is suggested. The suggested system is evaluated from energy, exergy, and exergoeconomic (3E) viewpoints. The impact of some prominent factors on the overall performance of the system is assessed. The proposed system can produce net power, and cooling load of 398.4 kW, 51.31 kW, respectively. Abstract: An innovative cogeneration power and cooling system is presented in which a solid oxide fuel cell (SOFC) is integrated with absorption and ejector refrigeration cycles. To assess the practicality of the suggested system, it is evaluated from energy, exergy, and exergoeconomic vantage points. The effects of key design parameters including SOFC input temperature, ammonia concentration, evaporation temperature, and hot temperature difference of the generator on the system's technical and economic performance are determined. The results revealed that the suggested system can generate overall electricity, and cooling load of 398.4 kW, 51.31 kW, respectively. Further, the energy and exergy efficiencies, and product cost rate of the system are 55.46%, 47.29%, and 106.7/GJ, respectively. Heat exchanger 3 is indicated as the major source of inefficiency by an exergy destruction rate of 106.2 kW. Furthermore, the results demonstrated that higher energy productivity is achievable by increasing the ammonia concentration, SOFC input temperature, and evaporation temperature. Moreover, results revealed that the higher the input temperature of the fuel cell, and the hot temperature difference of the generator are, the higher the exergy efficiency is obtainable. Considering the exergoeconomic assessment, it is observed that the product cost rate of the suggested CCP system can be decreased by the augmentation of the fuel cell input temperature, ammonia concentration, and evaporation temperature.